Analysis of the Relationship Between Tax Compliance and National Financial Health Indicators - Mela Novita Rizki; Fhikry Ahmad Halomoan Siregar; Oky Syahputra; Nangkula Utaberta (International Journal of Advanced Research, 2024)
This study examines the relationship between tax compliance and national financial health, focusing on how tax compliance rates influence key financial indicators such as public debt, fiscal deficits, inflation rates, and economic growth. Using data from a diverse sample of countries, both developed and developing, the study employs quantitative analysis through regression models to explore the impact of tax compliance on these financial outcomes. The results indicate that countries with higher tax compliance tend to have lower debt-to-GDP ratios, smaller fiscal deficits, stable inflation rates, and stronger economic growth. Institutional quality, digital tax systems, and tax morale are also identified as significant factors that enhance compliance and, in turn, improve financial health. Furthermore, the study highlights the long-term benefits of sustained tax compliance efforts and the importance of international cooperation in enhancing tax revenue collection. The findings provide valuable insights for policymakers aiming to improve fiscal stability by focusing on tax compliance as a key component of their economic strategies. Ultimately, the study demonstrates that effective tax systems are crucial for ensuring long-term financial stability and fostering sustainable economic growth.